Computational fluid dynamics analysis of middle ear pressure dynamics: Evidence for efficient pressure equalization during partial eustachian tube opening - Yanzhuo Zhang; Fang Guo; Hua Liang; Yuetang Wang; Lan Su; Xin Yang; Ranran Liu; Xin-ge Lu; Yongtao Tian; Chunhua Wang; Jin Wang (PLoS ONE, 2026)
Background Eustachian tube (ET) dysfunction is associated with middle ear pathologies; however, the quantitative relationship between ET opening and pressure equalization remains insufficiently characterized. Computational fluid dynamics (CFD) offers a robust tool for analyzing middle ear pressure dynamics, particularly in elucidating pressure equilibrium mechanisms under partial ET opening conditions. Objective This study aimed to investigate pressure dynamics in the tympanic cavity, mastoid antrum, and air cells during ET opening using CFD, to compare pressure distributions between full and partial openings, and to determine whether partial opening can achieve equilibration equivalent to full opening. Methods Eight normal temporal bones were reconstructed from high-resolution computed tomography scans of four healthy adults. ET openings were simulated at 10%, 30%, 50%, and 100% patency using CFD, and results were validated against in vivo Tubomanometry data. Pressure variations in the tympanic cavity, mastoid antrum, and air cells were monitored throughout the process. Mesh independence was verified to ensure reliability, and statistical analyses were conducted using SPSS 27.0, with P < 0.05 considered significant. Results CFD simulations revealed distinct pressure dynamics within the ET–middle ear system. Airflow velocity peaked at the narrow isthmus, generating a localized pressure drop. Effective middle ear pressure equilibration—across the tympanic cavity, antrum, and mastoid air cells—was achieved with partial ET opening in most cases: 30% opening sufficed for full equilibration in two ears, while 50% opening achieved complete equilibration in six. This equivalence to full patency was consistently observed during pressurization, stabilization, and depressurization phases. Conclusion Effective middle ear pressure equilibration can be achieved with partial ET opening (50%) in most cases (75% of ears). These findings provide valuable insight into middle ear physiology and its response under pathological conditions, offering a theoretical basis for optimizing the management of ET dysfunction.